Data quality and fitness for purpose of routinely collected data – a general practice case study from an electronic Practice-Based Research Network (ePBRN) - Liaw, Siaw-Teng (American Medical Informatics Association, 2011)
The practice-based research network (PBRN) is a resource to recruit research participants; conduct developmental and pilot studies; and coordinate multicentre research, teaching, clinical care and quality assurance programs. It is a community–based laboratory for translational, clinical and health services research. The mining of clinical information systems of PBRNs can be used to monitor performance at the service unit level. However, are the routinely collected data of ePBRNs fit for the abovementioned purposes? We describe the establishment and governance of an ePBRN which included general practice and community health and hospital units, The general practice data quality was examined, using diabetes as the context, for completeness, correctness and consistency and assessed on its fitness for research, audit and quality assurance purposes. The quality of social determinants data was generally good while risk factors data were variable. Issues and strategies for improving data quality are discussed.